2004
DOI: 10.1139/b04-012
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny ofBrayaandNeotorularia(Brassicaceae) based on nuclear ribosomal internal transcribed spacer and chloroplasttrnL intron sequences

Abstract: Sequence data from the nuclear ribosomal internal transcribed spacer (ITS) region and the chloroplast trnL intron were used to examine the evolutionary relationships and generic delimitations of Braya, Neotorularia, Dichasianthus, and Sisymbriopsis. Several species, especially the North American - Asian Braya (= Neotorularia) humilis (C.A. Mey.) B.L. Rob., were previously assigned to more than one genus. Sequence data were obtained from all Braya species, except Braya pilosa Hook., seven species of Neotorulari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 39 publications
1
27
1
1
Order By: Relevance
“…Despite the incomplete molecular knowledge of the Brassicaceae, a number of monophyletic clades or alliances have been identified based on Kropf (2002), Warwick et al (2002Warwick et al ( , 2004aWarwick et al ( , 2004bWarwick et al ( , 2005aWarwick et al ( , 2005b, , Warwick and Sauder (2005), and Beilstein et al (2006). Most of these major clades or alliances are recognized herein at the tribal level.…”
Section: Major Cladesmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the incomplete molecular knowledge of the Brassicaceae, a number of monophyletic clades or alliances have been identified based on Kropf (2002), Warwick et al (2002Warwick et al ( , 2004aWarwick et al ( , 2004bWarwick et al ( , 2005aWarwick et al ( , 2005b, , Warwick and Sauder (2005), and Beilstein et al (2006). Most of these major clades or alliances are recognized herein at the tribal level.…”
Section: Major Cladesmentioning
confidence: 99%
“…Although Hedinia also has the same leaf and trichome characters, he (1936) assigned it to the tribe Lepidieae because of having angustiseptate fruits. However, Warwick et al (2004b) demonstrated that there are no solid morphological grounds to maintain the smaller genera above as independent of Smelowskia.…”
Section: Major Cladesmentioning
confidence: 99%
See 1 more Smart Citation
“…These independent markers are widely applied in phylogenetic studies across the Brassicaceae and have helped in unraveling relationships within and among various taxa and major lineages (e.g., Franzke et al 1998Franzke et al , 2004Al-Shehbaz 2002, 2004;Mummenhoff et al 2004;Lihová et al 2004Lihová et al , 2006aWarwick et al 2004aWarwick et al , b, 2006bWarwick and Sauder 2005;Yue et al 2008;Carlsen et al 2009;Mummenhoff et al 2009;Jordon-Thaden et al 2010). …”
Section: Molecular Markersmentioning
confidence: 99%
“…Many examples of hybrid detection involve investigation of the additivity of nucleotides at single positions (polymorphic sites) of rDNA ITS sequences (e.g., Gravendeel & al., 2004;Koontz & al., 2004;Peterson & al., 2004;Warwick & al., 2004). An example of intraspecific ITS additivity can be found in Clausia aprica (Brassicaceae) where accessions of an intermediate group showed additivity, possibly indicating hybridization .…”
mentioning
confidence: 99%